The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2018
DOI: 10.3389/fchem.2018.00423
|View full text |Cite
|
Sign up to set email alerts
|

Electrocatalysis of Lindane Using Antimony Oxide Nanoparticles Based-SWCNT/PANI Nanocomposites

Abstract: This work describes the chemical synthesis of antimony oxide nanoparticles (AONPs), polyaniline (PANI), acid functionalized single-walled carbon nanotubes (fSWCNTs), and the nanocomposite (AONP-PANI-SWCNT) as catalyst for the trace detection of lindane. Successful synthesis of the nanomaterials was confirmed by Fourier transform infrared (FT-IR) spectroscopy, ultraviolet-visible (UV-Vis) spectroscopy, x-ray diffraction (XRD) spectroscopy, and scanning electron microscopy (SEM). Cyclic voltammetry (CV) and elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 66 publications
(95 reference statements)
0
6
0
Order By: Relevance
“…Information on the preparation and characterization of AONPs, PANI, fSWCNTs has been reported in our previous studies [ 39 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Information on the preparation and characterization of AONPs, PANI, fSWCNTs has been reported in our previous studies [ 39 ].…”
Section: Methodsmentioning
confidence: 99%
“…The resultant mixture was stirred at room temperature for 48 h to obtain a putty form of AONP-PANI-SWCNTs composite. This nanocomposite was dried overnight at 25 °C in order to evaporate the solvent [ 39 ]. The drop-cast method was used for the modification of the electrode.…”
Section: Methodsmentioning
confidence: 99%
“…From this perspective, conducting polymers combined with low loading of metallic species are good candidates for high-performance electrocatalysts due to their interesting structural and physical properties (Ghosh et al, 2015(Ghosh et al, , 2016(Ghosh et al, , 2017Wang et al, 2016a;Ramohlola et al, 2018). Among those polymers, polyaniline (PANI) has received tremendous attention in recent years in (bio)electrochemistry to be directly used as an electrode or indirectly as a supporting material (Wu et al, 2011;Silva et al, 2013;Boeva and Sergeyev, 2014;Xu and Minteer, 2014;Wang et al, 2016a;Cao et al, 2017;Torres et al, 2017;Feng et al, 2018;Masibi et al, 2018;Ramohlola et al, 2018;Shendkar et al, 2018;Bai et al, 2019). Torres and co-workers have shown that upon the introduction of Ni in a PANI-based electrode, the exchange current density (j 0 ) increases from 0.35 to 3.47 µA cm −2 , which indicates that the ability of electron transfer (driving force in electrocatalysis) is about one magnitude higher (Torres et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…40 The absorption peaks at 1612, 1611, 1425, and 1422 cm À1 correspond to the amine and imine groups in BC-PANI and BC-PANI-Cu. [41][42][43][44] The peaks at 1313 and 1290 cm À1 correspond to the protonated state of PANI, 45,46 while the peaks at 861 and 864 cm À1 can be attributed to the head-to-tail coupling of the aniline monomers. 47,48 Thus, the FT-IR analysis confirmed the presence of PANI in the BC-PANI-Cu membrane.…”
Section: Characterization Of Bc-pani-cumentioning
confidence: 99%